(untitled) (Eurasian Journal of Philology Science and Education, 2024)
The article is devoted to the analysis of the story "Meruert" of the outstanding public and statesman Zhurgenov Temirbek Karaevich. The authors consider the features of the spatial and temporal organization of this work. Based on a detailed analysis of the story, in the article the features of T.K. Zhurgenov’s worldview, his concept of being and personality are identified. The actuality of the research theme is due to the fact that this work has not previously been the object of special study. Meanwhile, the story "Meruert", along with the poem "Translator’s Fantasies", constitutes the literary legacy of Zhurgenov T.K. and it serves as an example of the versatility of his personality and talent. The purpose of this study is to reveal the artistic skill of Temirbek Karayevich, his attitude to reality, and the ability to penetrate into the essence of the problems raised by him, based on the analysis of the chronotope category at the level of ideological-thematic content, plot, and construction of the work. The article indicates that the space-time continuum of the story is characterized by multidimensionality. The events of the work unfold in several dimensions. Through the prism of the chronotope, the author comprehends the fate of the Kazakh girl, her place and role in society at the beginning of XX century. Using the example of the image of the main hero, T.K. Zhurgenov reflects on eternal and universal problems, the peculiarities of the historical epoch. The work is filled with deep drama. T.K. Zhurgenov reveals the contradictions of the era he portrays. Great attention in the story is paid to the inner world of the characters, the space of their soul and consciousness. The theoretical and practical significance of this research lies in the fact that its results can be used not only in the process of studying the heritage of T.K. Zhurgenov, but also Kazakh literature of the early XX century. Key words: a work, a story, an author, chronotope, a hero, a problem, an image.